On the Pleasure of Admiring. - Corey, Elizabeth C. (First Things: A Monthly Journal of Religion & Public Life, 2026)
The article focuses on the value and practice of admiration as a countercultural and enriching alternative to constant self-promotion. Topics include the cultivation of self-awareness, the development of connoisseurship in recognizing excellence, and the importance of acknowledging both our own and others' fallibility in order to admire authentically.